Effect of Yonidhavan on Different Gynaecological Diseases - A Retrospective Study (International Journal of Ayurveda and Pharma Research, 2024)
Gynecological diseases are increasing day by day. Among all, female genital infections bear a major component. It carries the specific attention of underlying diseases such as vaginitis, cervical erosions PIDs, to malignancies. Ayurveda highlights these disorders under Yonivyapadas. Classics have highlighted 20 types of Yonivypadas where pathogenesis takes place in genital areas. Local treatments such as Yonidhavan, Picu, Varti are described for the same. Yonidhavan refers to drug delivery through genital areas. The medicated fluid of Yonidhavan helps to clean genital areas, reduce inflammation and help to regrowth healthy tissue.  Understanding these, a retrospective study on the effect of Yonidhavan with Panchawalkal Kwath for a sample of 100 patients was done for 1 year. Analysis of the symptoms as well as the result, with clinical evidence and statistical evaluation, proved that overall Yonidhavan gave excellent outcomes in 94.9% patients in relieving the symptoms. The therapy proved to be promising on criteria such as per vaginal discharge (Srava), tenderness (Sparasahatwa), and tissue swelling (Shoph). It proved most significant on per vaginal profuse discharge (96.5%) and tenderness (Sparasahatwa) (74.3%). The study revealed that no recurrence of the symptoms was noticed after one year in 73% of the patients. Twenty-two percent of patients showed recurrence of symptoms in one year. The use of Panchawalkal Yonidhavan not only gave symptomatic relief but helped to cure Yonivypadas. Yonidhavan proved helpful, economical, and accessible Ayurvedic treatment.